Sposoby mówienia o "niepamięci" we współczesnym dyskursie (szkic do badań językowego obrazu "niepamięci") = Ways of talking about "oblivion" in contemporary discourse (A sketch for the study of the linguistic image of "oblivion") - Uździcka, Marzanna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The problems of the article are part of and complementary to the Polish discourse of memory studies. The category of oblivion in question appears mainly when considering memory, so this discussion is a contribution to the linguistic image of oblivion in contemporary discourse. The material basis consists of collocations extracted from the National Corpus of Polish Language with the component non-memory and its grammatical forms: non-memory, non-memory for the years 1989-2010.
Keywords: pamięć; niepamięć; dyskurs pamięcioznawczy; kolokacja; metafora pojęciowa; memory; oblivion; memory science discourse; collocation; conceptual metaphors